Comparing COVID-19-related Morbidity and Mortality Between Patients With and Without Substance Use Disorders: A Retrospective Cohort Study - Angela McLaughlin; Rebecca Burns; Morgan Ryan; Wafaa Abbasi; Leah Harvey; Jacqueline Hicks; Pranay Sinha; Sabrina A Assoumou (SAGE Publishing, 2023)
Objectives: People with substance use disorders (SUD) are suggested to have higher risk of hospitalization, intubation, or death from coronavirus disease 2019 (COVID-19), although data are mixed. Little is known about other COVID-19-related complications in this group. We compared morbidity and mortality among individuals with and without SUD who were admitted to an urban safety net hospital with COVID-19 early in the pandemic, contemporaneous to other published studies on this subject. Methods: We performed a retrospective study of patients ⩾18 years old admitted with COVID-19 from March 16th to April 8th, 2020. SUD included alcohol, opioid, cocaine, amphetamine, and benzodiazepine use disorders and was identified using diagnostic codes, free text clinical documentation, and urine drug screens. The primary outcome was inpatient mortality. Secondary outcomes included clinical complications (eg, secondary infections, venous thromboembolism) and resource utilization (eg, mechanical ventilation, length of stay). We used multivariable regression to assess the relationship between SUD and mortality. Results: Of 409 patients, the mean age was 56 years and 13.7% had SUD. Those with SUD were more likely to be male, have experienced homelessness, have pulmonary disease or hepatitis C, or use tobacco or cannabis. After multivariable analysis, SUD was not associated with mortality (aOR 1.03; 95% CI, 0.31-3.10). Secondary outcomes were also similar between groups. Conclusions: Our findings suggest that persons with and without SUD have similar COVID-19-related outcomes. Previously reported increased COVID-19 complications may be from medical comorbidities.